Coping with poverty and institutionalised practices: Tank-irrigated cultivation in Kolar District, Karnataka - Lars Engberg-Pedersen (Danish Institute for International Studies (DIIS), 2011)
Though in decline, tank irrigation is still an important characteristic of rural social life in many parts of South India. It is of particular importance to the poor being dependent on agriculture, while rich landowners increasingly concentrate their investments and income on non-rural activities. Based on fieldwork in two communities, this paper explores the strategies of the poor and the management of tank irrigation. It establishes the main concerns and priorities of the poor and describes why the poor regard well-managed tank irrigation as a significant asset. Moreover, it studies two sets of institutionalised practices in relation to tank management, namely those related to the distribution of water from the tank and those related to the use of water when water is scarce. Both sets of practices have stable and disputed elements, and given the particular circumstances they are the object of more or less intense negotiations. Furthermore, the practices are influenced by contextual changes including the changing caste relations. Overall, the paper argues that different and equally legitimate logics can be applied to the distribution of water and this provides some opportunities for the poor to influence tank management to their advantage.
Keywords: 300; Agrarboden; Bewässerung; Armut; Indien